2004
DOI: 10.1073/pnas.0400776101
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin regulation of endometrial structure and function in the rhesus monkey

Abstract: Despite the documented importance of the protein hormone relaxin in reproduction in various mammalian species, the role of relaxin in human reproduction is poorly understood, largely because of the lack of studies in women or in suitable non-human primate models. Here we describe the establishment of a nonhuman primate model of early human pregnancy and its use in defining the actions of relaxin. Results demonstrate that relaxin exerts dramatic uterine effects including pronounced increase in uterine weight an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 54 publications
3
88
1
3
Order By: Relevance
“…Isolated HUVEC cells were reported to respond to relaxin with increased the production of nitric oxide synthase II and increased nitric oxide generation (51). Relaxin was also shown to induce vascular endothelial growth factor and procollagenase expression in human endometrial cells and to stimulate blood vessel formation in the primate endometrium (52,53). Here, we show for the first time a direct angiogenetic effect of RLN2 by promoting endothelial tube formation of HUVEC by RLN2.…”
Section: Discussionmentioning
confidence: 61%
“…Isolated HUVEC cells were reported to respond to relaxin with increased the production of nitric oxide synthase II and increased nitric oxide generation (51). Relaxin was also shown to induce vascular endothelial growth factor and procollagenase expression in human endometrial cells and to stimulate blood vessel formation in the primate endometrium (52,53). Here, we show for the first time a direct angiogenetic effect of RLN2 by promoting endothelial tube formation of HUVEC by RLN2.…”
Section: Discussionmentioning
confidence: 61%
“…Other investigators have observed that the effect of relaxin on MMP regulation appears to be cell-type specific. For example, the upregulation, 10,28 downregulation 39,40 and biphasic regulation 27 of MMPs by relaxin have been reported before. In tumor biology, MMPs have been implicated in a variety of processes: a) the degradation of the ECM allowing for cell migration; 41 b) the alteration of the ECM microenvironment resulting in changes of cellular behaviour; 41 and c) the modulation of biologically active molecules by direct cleavage, release from bound stores or modulation of the activity of tissue inhibitors of MMPs (TIMPs).…”
Section: Discussionmentioning
confidence: 70%
“…However, a similar decidualisation response can also be induced by relaxin alone, acting through RXFP1, but within a much shorter time-frame of only 2-3 days . Moreover, studies using monkeys have shown that supplementary relaxin in vivo is able to specifically induce a thickening of the endometrium, improved vascularization, and reduced pregnancy loss (Goldsmith et al, 2004;Hayes et al, 2004;Einspanier et al, 2009), consistent with a very positive impact on implantation and placentation. Also in women, it has been shown that there is a good association between mid-pregnancy levels of circulating relaxin, reduced spontaneous abortion, and increased blood flow (Jauniaux et al, 1994;Anumba et al, 2009).…”
Section: Relaxin and The Endometrium In Early Pregnancymentioning
confidence: 93%
“…Goldsmith et al, 2004). It appears to achieve this by a local induction of vascular endothelial growth factor, VEGF, for example by endometrial stromal cells (Unemori et al, 1999).…”
Section: Relaxin and The Cardiovascular Systemmentioning
confidence: 99%